SYNTHESIS AND CHARACTERIZATION OF Li4Ti5O12 WITH SOL GEL METHOD AS A LITHIUM ION-BATTERY ANODE MATERIAL - Slamet Priyono; Ilma Nuroniah; Achmad Subhan; Edi Sanjaya; Bambang Prihandoko (Jurnal Sains Materi Indonesia, 2019)
SYNTHESIS AND CHARACTERIZATION OF Li4Ti5O12 WITH SOL GEL METHOD AS A LITHIUM ION-BATTERY ANODE MATERIAL. Synthesis of anode Li4Ti5O12 material has been carried out using the sol gel method. The synthesis is carried out with variations in sintering temperatures at 500 oC, 600 oC, 700 oC dan 800 oC. Characterization carried out includes testing thermal analysis to determine the optimum temperature for sintering, XRD (X-ray Diffraction) to find out the phase formation of Li4Ti5O12, Scanning electron microscope (SEM) to analyse the morphology formed, testing Cyclic voltammetry, charge-discharge and Electrochemical Impedance Spectroscopy (EIS) is carried out to find out the elec- trochemical performance. From the results of characterization of thermal and XRD analyses, the optimum temperature for synthesis is 800oC with small impurity content. The results of SEM characterization show that the morphology of the sample is not homogeneous, and the particles are agglomerated. The resulting electrochemical performance increases along with the increase in temperature for sintering, including voltammogram graphs, diffusion coefficient values, electrical conductivity and charge-discharge capacity. Of all the samples, the LTO sintered at 800oC shows good electrochemical performance with a sharp and good voltammogram graph, diffusion coefficient value of lithium ion is 1.58 × 10-9 cm2s-1, electrical conductivity of 0.6282 S/cm and the discharge capacity given is 78,07 mAh/g.